Comparison of multiple doses of corticosteroids in Kawasaki disease: a Bayesian network analysis - Li, Xuan; Tang, Xuan; Yang, Daoping; Hou, Miao; Xu, Qiuqin; Tang, Yunjia; Wang, Bo; Huang, Hongbiao; Chen, Ye; Liu, Zhiheng; Qian, Guanghui; Lv, Haitao (Frontiers in Pharmacology, 2025)
BackgroundKawasaki disease (KD) is a leading cause of acquired heart disease in children, with coronary artery lesion (CAL) as a major complication. Although intravenous immunoglobulin (IVIG) remains the cornerstone of therapy, corticosteroids continue to play an important role in the management of IVIG-resistant, high-risk, or severe Kawasaki disease. Nevertheless, the optimal dosing strategies and differential therapeutic effects of corticosteroids in children with distinct clinical subtypes of KD remain poorly understood, particularly in those at highest risk.MethodsWe conducted a Bayesian network meta-analysis of five regimens: intravenous immunoglobulin alone (IVIG-alone), medium-dose methylprednisolone alone (MDMP-alone), high-dose methylprednisolone alone (HDMP-alone), IVIG-plus-low-dose methylprednisolone (IVIG-plus-LDP), and IVIG-plus-HDMP. Data from randomized controlled trials (RCTs) through December 2024 were included.ResultsIVIG-plus-HDMP ranked highest for preventing treatment resistance and reducing fever in initial and refractory KD [Surface Under the Cumulative Ranking Curve (SUCRA) 0.79]. IVIG-plus-LDP had the highest probability of reducing coronary artery dilation (CAD) incidence (SUCRA 0.89). Corticosteroid-related side effects (e.g., bradycardia, hypertension) were mild, transient, and reversible across all regimens, with no severe adverse events reported.ConclusionIVIG-plus-HDMP is the most effective therapy for acute symptom control in KD, particularly in high-risk or IVIG-resistant cases, while IVIG-plus-LDP appears superior for long-term prevention of coronary complications in the general KD population. Treatment selection should be individualized based on patient risk profile and treatment priorities, balancing rapid symptom management against long-term coronary outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022339937.